Enhanced resilience through the use of seasonal forecasts implemented by the National Civil Aviation and Meteorology Agency of Senegal (ANACIM) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The use of seasonal forecasts is enhancing farmers' resilience by increasing farm productivity, profitability, and income in Senegal. This is a new strategy being implemented by the National Civil Aviation and Meteorology Agency of Senegal (ANACIM)